KEBERHASILAN OPERASI TRABEKULEKTOMI PADA GLAUKOMA SUDUT TERBUKA PRIMER PERIODE 2019-2021 - Radilia, Fasya; Rifada, R. Maula; Kartiwa, R. Angga (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2023)
Introduction: Glaucoma represents a group of diseases defined by a characteristic optic neuropathy that is consistent with remodeling of the connective tissue elements of the optic nerve head and with loss of neural tissue associated with the eventual development of distinctive patterns of visual dysfunction. The most common surgery for glaucoma treatment is trabeculectomy, which in principle is done by creating a new channel that drains the aqueous humor, and return the intraocular pressure to normal levels. Objective: This study aimed to know the success rate of trabeculectomy in primary open-angle glaucoma. Methods: This study used a retrospective descriptive research method and was conducted in the Medical Records Center of the Cicendo National Eye Hospital, Bandung City with a data collection period of 21 July 2022 – 6 September 2022. The data collection process was carried out by looking at secondary data from medical records of patients with primary open-angle glaucoma for the period January 2019 – December 2021. Results: Mean IOP decreased from 32.6±12.9 before surgery, to 19.8±10 one week after surgery, and 18.8±7.3 one month after surgery. The overall success rate reaches 82.1%. Conclusions: The success rate for open-angle glaucoma treated with trabeculectomy at Cicendo National Eye hospital is considered good with a total success rate of 82.1% with or without anti-glaucoma medication to control IOP after surgery.